Pemberdayaan Guru Sekolah Dasar Muhammadiyah dalam Pembudayaan Literasi Numerasi Era Pandemi Covid-19 - Meggy Novitasari; Sutama Sutama; Sabar Narimo; Harsono Harsono (Universitas Muhammadiyah Surakarta, 2023)
Numeracy is a strong foundation for attitude and action during the Covid-19 period. The cultivation of numeracy literacy at SD Muhammadiyah PK Boyolali has not met expectations. There are three objectives of this activity. 1) Teachers master the strategy of cultivating numeracy literacy. 2) The teachers apply the strategy of cultivating numeracy literacy well, students are happy and accustomed to learning numeracy literacy. 3) There is an increase in students' numeracy literacy skills. The activity was carried out at SD PK Boyolali and Banyudono Boyolali, January-June 2021. Participants were 25 teachers and 114 students. The implementation method goes through three stages, namely workshops, implementation assistance and assessment. Results of the activity: 1) The teachers mastered the strategy of cultivating numeracy literacy well, shown in the learning tools. 2) The teachers apply the strategy of cultivating numeracy literacy by a) getting used to various strategies for various questions, b) giving enough time to try questions, c) inviting them to solve problems in other ways, d) inviting them to look at other possibilities, e) when facing difficult problems not avoided but using time to repeat and work on more questions, and f) flexibility in problem solving. The students are happy and accustomed to learning numeracy literacy by, a) practicing consistently, disciplined and continuously, b) studying mathematics material outside the school curriculum, c) avoiding looking at answers before trying to work on questions, d) practicing writing down answers systematically, and e) try to solve the problem in another way. 3) There is an increase in students' numeracy literacy skills, both in personal, socio-cultural, and scientific contexts.